PROTECTION OF PATIENT RIGHTS BY THE PATIENT RIGHTS OMBUDSMAN - Jacek, Anna; Ożóg, Katarzyna (Review of European and Comparative Law, 2016)
The Patient Rights Ombudsman has become another body for the investiga-tion of patients’ claims . For independence from the State bodies, the Ombudsman should be a single, term-limited body appointed and dismissed by the Sejm . He can pass the case to the public prosecutor’s office, appoint experts and request for expertise . To sum up, the Ombudsman is one of the mechanisms to ensure respect for patient rights . However, the act on PR does not limit the scope of the constitu-tional powers of ombudsmen, who may also take action in the area of health pro-tection . The ombudsman can ask them to take action within their competence . The analysis of the reports of the Office of the Patient Rights Ombudsman and the views of the representatives of the doctrine of patient rights, allows to draw some conclusions concerning the violations of the rights of patients . A particu-larly widespread phenomenon was violation of the right to consent to the provi-sion of health benefits, as well as restricting access to health services . Medical personnel do not respect the rights of the patient to the respect for their intimacy and dignity, and the right to information . Patients are not aware of the process and way of treatment and do not know the refund policy . Most cases of violations in Poland was due to ignorance of the applicable laws . Patients’ claims relating to their rights will improve the quality of provided health benefits and determine the 10position of the patient as an equal participant in the health system . Patients have unparalleled access to medical knowledge via modern means of communication, they have never had such possibilities for controlling the regularity of medical actions . The effect of these changes is an increase in the number of claims against the medical staff the entities providing medical services . To sum up, the execution of patient rights requires continuous education among medical personnel, which should be carried out on the initiative of the heads of the entities and professional authorities . We should also improve awareness of patients by conducting national information and communication actions.